Strategi Digital Storytelling dalam Membangun Interaksi Audiens pada Konten YouTube NERROR @Nessie Judge - Ridho Avis; Amin Aminudin (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
The development of digital media, particularly YouTube, has transformed communication patterns and information consumption from passive reception to more participatory engagement. As an audiovisual platform, YouTube enables creators to build audience involvement through narratives that are delivered in personal and persuasive ways. Amid increasingly intense competition among content creators, digital storytelling has emerged as a strategic approach to attract attention while fostering audience interaction. Nessie Judge is one of the creators who consistently applies digital storytelling through her NERROR content on YouTube. This study aims to explore the digital storytelling strategies employed by Nessie Judge and analyze how these strategies construct audience interaction within the comment section. This research adopts a descriptive qualitative approach, using a single NERROR video selected purposively as an information-rich and analytically relevant case. Data were collected through non-participant observation of both the video’s narrative structure and the dynamics of audience responses in the comment section. The data were analyzed using thematic analysis to identify storytelling patterns and forms of audience engagement. The findings indicate that the digital storytelling strategy is constructed through a coherent and emotionally driven narrative structure, reinforced by tempo management, contextual visual and audio elements, and a personal communication style that fosters a sense of closeness. Audience immersion in the narrative is reflected in reflective and discursive responses that appear asynchronously in the comment section. These findings demonstrate that long-form storytelling practices on YouTube can sustain audience attention while simultaneously generating interactive engagement within the digital public sphere.